2014
DOI: 10.1177/1557988314532824
|View full text |Cite
|
Sign up to set email alerts
|

How Do African American Men Rate Their Health Care? An Analysis of the Consumer Assessment of Health Plans 2003-2006

Abstract: African American (AA) men remain one of the most disconnected groups from health care. This study examines the association between AA men's rating of health care and rating of their personal physician. The sample included 12,074 AA men aged 18 years or older from the 2003 to 2006 waves of the Consumer Assessment of Healthcare Providers and Systems Adult Commercial Health Plan Survey. Multilevel models were used to obtain adjusted means rating of health care systems and personal physician, and the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…2). A total of 19 articles met our inclusion criteria: 10 studying clinical outcomes of care19–28 and 9 studying quality outcomes of care 29–37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). A total of 19 articles met our inclusion criteria: 10 studying clinical outcomes of care19–28 and 9 studying quality outcomes of care 29–37…”
Section: Resultsmentioning
confidence: 99%
“…Statistically significant findings of studies examining associations of CAHPS ratings with quality outcomes are summarized in Table 3. We identified 9 studies investigating quality outcomes and 8 found significant associations 29,31–37. Studies examining quality outcomes were completed between 2001 and 2019 and were a combination of cross-sectional (n=7)29,32–37 and prospective cohort (n=2) 30,31.…”
Section: Resultsmentioning
confidence: 99%
“…Other research has suggested gender differences in the role of religious involvement in alcohol use in African Americans (Bowie et al, 2006). Findings around gender differences could have implications for health promotion interventions, particularly given that African American men remain one of the most medically underserved and understudied groups (Elder et al, 2014). It is important to gain insights on the role of religion in the health of African Americans (Ellison et al, 2010) and to apply these insights to health-promotion interventions in this often-overlooked group.…”
Section: Present Studymentioning
confidence: 99%
“…Men’s health is a relatively new research area; however, substantial strides have been made to advance the science in terms of health behaviors, health status, and interaction with the health-care system ( Elder et al, 2015 ; Gilbert et al., 2015 ; Griffith, Bergner, et al, 2018 ; Griffith, Cornish, et al, 2018 ; Mui et al, 2018 ; Sohn et al, 2017 ; Thorpe et al, 2017 ; Valdez et al, 2019 ). Overall, the life expectancy for men in the United States has shown positive trends since 1980 increasing by 6 years to 76.4 ( National Center for Health Statistics, 2018 ).…”
mentioning
confidence: 99%
“…The uninsured rate has declined since 2010 for nonelderly women and men from 19% to 24%, respectively; however, the uninsured rate for men (14%) remains higher compared to women (11%) ( Kaiser Family Foundation, 2020 ). This is of some importance as health insurance is a predictor of health status and the health of men tends to be poor ( Elder & Griffith, 2016 ; Elder et al, 2015 ; Gilbert et al, 2016 ). Even with the decrease in uninsured rates among men, one in five men aged 18–64 years experience difficulty in paying medical bills ( Kaiser’s Men’s Health Survey, 2015 ).…”
mentioning
confidence: 99%